Effects of task variations on language productivity, syntactic complexity, and stuttering in children who stutter. - Sasisekaran, Jayanthi; Lei, Xiaofan (Clinical Linguistics & Phonetics, 2024)
Purpose. The aim of this preliminary study was to compare the effects of variations in task demands on: (a) language productivity in sentences categorised into stuttered vs. non-stuttered sentences; (b) syntactic complexity in stuttered vs. non-stuttered sentence categories, and (c) stuttering and typical disfluencies in school-age children who stutter (CWS). Language Sample Analysis (LSA) was conducted on samples from three tasks – Conversation, fable retell, and critical thinking based on the fables. Methods. Participants were 14 CWS categorised into younger (9 to 12-year-olds, n = 8) and older age groups (13 to 15-year-olds, n = 6). The Computerized Language ANalysis program was used to conduct language and disfluency analyses. Repeated measures analysis of variance and nonparametric statistical analyses were used to investigate: (a) Language productivity in total number of words and sentences by task and sentence category; (b) Syntactic complexity at the word- (use of metacognitive verbs), phrase- (use of verb phrases), and utterance (Mean Length of Utterances in words, MLUw) levels by task and sentence category; and (c) Disfluencies measured using % stuttered syllables (%SS) and % typical disfluencies (%TD). Results and Conclusions. Task effects in language productivity did not differ by sentence category and suggested limited influences of propositionality and volubility in stuttering. In contrast, higher syntactic complexity was obtained in the stuttered compared to non-stuttered sentences at the word, phrase, and utterance levels and it was the same task – conversation, that elicited the effect. Additionally, variations in task demands did not result in significant differences in %SS. The findings inform assessment planning with the selection of tasks guided by task demands and assessment requirements.